2020
DOI: 10.1002/jbt.22649
|View full text |Cite
|
Sign up to set email alerts
|

MEG3 aggravates hypoxia/reoxygenation induced apoptosis of renal tubular epithelial cells via the miR‐129‐5p/HMGB1 axis

Abstract: The apoptosis of renal tubular epithelial cells (TECs) during ischemia/reperfusion (I/R) facilitates the progression of acute kidney injury (AKI). This study aimed to probe the role of long noncoding RNA maternally expressed 3 (MEG3) in I/R‐induced apoptosis of TECs. In this study, with CoCl2 and hypoxia/reoxygenation treatments, cell models were established to mimic I/R using the human kidney tubular cell line HK‐2. In HK‐2 cells, expression of MEG3 detected using quantitative real‐time polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…MiR‐92d‐3p suppresses renal fibrosis and inflammation of HG‐stimulated HK‐2 cells by inhibiting the C3/HMGB1/TGF‐β1 pathway during DN progression 52 . Long noncoding RNA maternally expressed 3 (MEG3) exacerbates the hypoxia/reoxygenation‐stimulated HK‐2 cell apoptosis via the miR‐129‐5p/HMGB1 axis 53 . In this study, HMGB2 was found to be overexpressed in HG‐stimulated HK‐2 cells and in renal tissues of STZ‐induced diabetic mice, suggesting that HMGB2 may be implicated in DN development.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐92d‐3p suppresses renal fibrosis and inflammation of HG‐stimulated HK‐2 cells by inhibiting the C3/HMGB1/TGF‐β1 pathway during DN progression 52 . Long noncoding RNA maternally expressed 3 (MEG3) exacerbates the hypoxia/reoxygenation‐stimulated HK‐2 cell apoptosis via the miR‐129‐5p/HMGB1 axis 53 . In this study, HMGB2 was found to be overexpressed in HG‐stimulated HK‐2 cells and in renal tissues of STZ‐induced diabetic mice, suggesting that HMGB2 may be implicated in DN development.…”
Section: Discussionmentioning
confidence: 99%
“…At the outer mitochondrial membrane, the MCL-1 isoform antagonizes apoptosis like other anti-apoptotic BCL-2 molecules, whereas the amino-terminal isoform of MCL-1 imported into the mitochondrial matrix promotes normal mitochondrial fusion, ATP production, membrane potential, respiration, cristae ultrastructure and oligomeric ATP synthase activity 66 . LncRNA MEG3(maternally expressed gene 3), a tumor suppressor, has been shown to be involved in the development of cancer 67 - 68 . And Gong A et al found that IncRNA MEG3 mediates ST3Gal1 to regulate EGFR phosphorylation, which will downregulate Bcl-2 and prcaspase-2 expression,upregulate caspase-2 and cytochrome c release 69 , leading to mitochondrial dysfunction and inducing apoptosis in ccRCC cells.…”
Section: Lncrnas and Mitochondrial Dynamicsmentioning
confidence: 99%
“…In two recent studies, HK2 cells under hypoxia increased HIF-1α levels through the LncRNA PRINS and its interaction with CCL5 [ 58 ]. The LncRNA MEG3 was also found to be elevated in human tubuloepithelial cells, aggravating hypoxia/reoxygenation induced apoptosis throughout regulation of the miR-129-5p/HMGB1 axis [ 59 ]. All these results confirm the emerging role of LncRNAs in the pathophysiology of I/R renal injury and their possible use as biomarkers in this pathological setting.…”
Section: Role Of Lncrnas In Renal Diseasesmentioning
confidence: 99%